Performance of Different Size True Potato Seed Seedling Tubers at Khumaltar (Nepal Agriculture Research Journal, 2010)
A field study was carried out at Khumaltar-Lalitpur, during 2002-2004 to evaluate and comparethe performance of different sizes of seedling tubers (1-5 g, 5-10 g, 10-20 g and 20-40 g) of truepotato seed (TPS) with whole and half cut seed tubers of Desiree of 20-40 g size at 60- × 25-cmspacing. Percent emergence, plant height, ground cover by foliage, stems/plant, number of tubersper plant, marketable and total yields were significantly increased with the increase in seedlingtubers weight as compared to whole and half cut seed tubers of Desiree. Late blight(Phytophthora infestans L.) disease was quite low in the TPS crops than Desiree. Both wholeand half cut seed tubers of Desiree produced significantly higher average per tuber weight.Uniformity of the tubers harvested from different sizes of seedling tubers was statisticallysimilar and tubers from Desiree were statistically uniform as compared to seedling tubers. Thethree years result suggests that more than 1 g size seedling tubers can be successfully used forpotato production as from the seed tubers of any standard variety.Key words: Desiree; seedling tuber; tuber size; tuber yieldDOI: 10.3126/narj.v6i0.3341Nepal Agriculture Research Journal Vol.6 2005 pp.28-34